FREQUENCY OF METABOLIC ACIDOSIS IN EARLY ONSET SEPSIS IN NEONATES PRESENTING TO TERTIARY CARE HOSPITAL - Shafique, Mehwish; Nizam, Rabia; Shaheen, Anila; Ashraf, Iqra; Masood, Shadab; Imtiaz, Mehwish (Journal of Ayub Medical College Abbottabad, 2024)
Background: Early Onset Neonatal Sepsis (EONS) is a serious blood infection mainly microbial in nature and has worse health complications. Metabolic acidosis is one of such complications that occur due to acid-base imbalance and may result in lectic acidosis, myocardial depression, hypo-perfusion, shock and even death in severe cases. Despite of its significance, limited local literature is available in this regard. Aims were to determine frequency of metabolic acidosis in early onset neonatal sepsis among neonates presenting in a tertiary care hospital. This was cross sectional study. Methods: Present study was conducted in department of Children's Hospital and Institute of Child Health Lahore. The data was collected through Non probability consecutive sampling from 242 neonates aged ‰¤72 hours of either gender diagnosed as EONS. Data was entered and analyzed in SPSS 22. For association, Chi-square test was applied and p-value ‰¤0.05 was considered as significant. Results: The mean age of patients was 36.49±18.33 hours with 137(56.61%) male and 105(43.39%) female cases in this study. The frequency of metabolic acidosis was 67(27.69%) of the cases with no association with age, birth weight, gestational age and gender (p-values >0.05). Practical Implication: Even recently, no local study has published the frequency of metabolic acidosis or found its association directly with EONS in Pakistan. Therefore, metabolic acidosis if found in EONS neonates, then in future every patient with early onset sepsis should be screened and can be managed timely. Conclusion: It is concluded that very high statistics of metabolic acidosis, i.e., 27.69% so every patient with early onset sepsis should be screened for metabolic acidosis to reduce worse health outcomes.